Integrated proteome and transcriptome analyses revealed key factors involved in tomato (Solanum lycopersicum) under high temperature stress. (19th August 2020) - Ding, Haidong; Mo, Shuangrong; Qian, Ying; Yuan, Guibo; Wu, Xiaoxia; Ge, Cailin
Abstract: High temperature (HT) is an important environmental factor affecting crops growth, development, and yield. Transcriptome and proteome technologies developed in recent years can provide deeper and more reliable data to decipher the mechanisms of HT response. In the present study, the transcriptome analysis with RNA sequencing (RNA‐Seq) and integrative analysis on obtained proteomic data were performed in tomato ( Solanum lycopersicum ) leaves under HT stress (42°C for 4 hr). In total, 3, 531 differentially expressed genes (DEGs) and 268 differentially expressed proteins (DEPs) were explored. The quantitative data were validated by qRT‐PCR and parallel reaction monitoring (PRM). Upon mapping of the DEGs/DEPs to the KEGG pathway database, "protein processing in the endoplasmic reticulum" was found to be the most significant enrichment pathway both at the transcriptional and protein levels, suggesting that endoplasmic reticulum stress may play a central role in HT tolerance. Furthermore, transcriptome‐proteome integrative analysis revealed 91 genes shared both in DEGs and DEPs, of which 79 correlations with the same changing trends were most associated with stress response and protein folding. Among these, a HT response gene designated SlBAG5 of unknown function received attention. The full‐length of SlBAG5 was cloned and ectopically overexpressed in Arabidopsis, which displayed thermosensitive phenotype. Taken together, this work provides deep insight into the molecular mechanisms of plant thermotolerance and also facilitates the identification of the key potential genes/proteins for HT response. Abstract : The integrated analyses of transcriptome and proteome showed that transcriptome data had greater abundance than proteome data. "protein processing in the endoplasmic reticulum" might play a central role in HT tolerance. SlBAG5 is an important cochaperone for thermotolerance. By integrating the analysis of transcriptomes and proteomes, the potential key HT‐tolerant genes can be exploited for further study and efforts to develop crops withstanding the impacts of a changing climate.